2018
DOI: 10.1161/circulationaha.117.030190
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Comparisons of Double-Dose Clopidogrel or Adjunctive Cilostazol Versus Standard Dual Antiplatelet in Patients With High Posttreatment Platelet Reactivity

Abstract: URL: https://www.clinicaltrials.gov. Unique identifier: NCT01779401.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
54
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 75 publications
(60 citation statements)
references
References 45 publications
1
54
0
Order By: Relevance
“…In the ISAR‐HPR registry, retreatment with clopidogrel, switch to prasugrel, and reassessment of platelet function were associated with a significant decrease in the incidence of adverse events when compared to historical controls . The CREATIVE randomized study indicated that the intensified antiplatelet strategy with adjunctive use of cilostazol significantly improved clinical outcomes of patients with low response to clopidogrel . In the current study, patients with HPR to clopidogrel were randomized to receive ticagrelor or to continue on clopidogrel.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…In the ISAR‐HPR registry, retreatment with clopidogrel, switch to prasugrel, and reassessment of platelet function were associated with a significant decrease in the incidence of adverse events when compared to historical controls . The CREATIVE randomized study indicated that the intensified antiplatelet strategy with adjunctive use of cilostazol significantly improved clinical outcomes of patients with low response to clopidogrel . In the current study, patients with HPR to clopidogrel were randomized to receive ticagrelor or to continue on clopidogrel.…”
Section: Discussionmentioning
confidence: 94%
“…For HPR patients, a personalized antiplatelet treatment with selective intensification of P2Y12 receptor inhibition has been investigated in several previous studies . In the ISAR‐HPR registry, retreatment with clopidogrel, switch to prasugrel, and reassessment of platelet function were associated with a significant decrease in the incidence of adverse events when compared to historical controls .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Results of the Clopidogrel Response Evaluation and AnTi-platelet InterVEntion in High Thrombotic Risk PCI Patients (CREATIVE) Trial which compared DDC with that of the standard DAPT or cilostazol associated TAPT showed the latter to significantly improved outcomes [14]. However, no significant difference was observed when DDC was compared to the standard DAPT.…”
Section: Discussionmentioning
confidence: 99%